Clinical decision-making in low back pain: age effects on prescribing, imaging and guideline adherence in primary care - Driton Tifeku; Valon Livoreka (Revista Pesquisa em Fisioterapia, 2026)
BACKGROUND: Managing low back pain (LBP) in primary care is challenging, with variations in clinician practices. Patient age may influence prescribing, diagnostic imaging, and guideline adherence. This cross-sectional study examines associations between age and medication prescribing or radiography use and identifies predictors of adherence to LBP guidelines in Kosovo's primary care. METHODS: We analyzed data from 133 adult patients (≥18 years) with non-traumatic LBP at Primary Care Center (Jan.-June 2025). Eligibility: consecutive patients providing informed consent, excluding pregnancy-related LBP, cognitive impairment, or red flags (e.g., trauma, cancer). Instruments: standardized questionnaire on demographics, medication type (NSAIDs, muscle relaxants, opioids, none), radiography use (past 12 months), and clinical justification (e.g., red flags); 4-point adherence score (0 = non-adherent to 3 = ideal). Chi-square tests, Pearson correlations, and ordinal logistic regression were applied using SPSS v28. RESULTS: No age-group differences in medication (χ² = 1.813, p = 0.612). Radiography rate: 11 (8%). Adherence predictors: age (OR = 1.025, p = 0.037), clinical justification (red flags OR = 3.320, p = 0.008), radiography frequency (OR = 0.861, p = 0.061) (model: χ² = 111.742, p < 0.001). CONCLUSION: Age, clinical justification, and radiography frequency predict moderate LBP guideline adherence. Targeted training on red flags and non-pharmacological therapies could enhance compliance and reduce low-value care in resource-limited settings.